La alimentación del niño con parálisis cerebral un reto para el nutricionista dietista. Perspectivas desde una revisión (2010)
ABSTRACT: Cerebral paralysis defined the syndrome for damage of nervous system, it could happen during critical periods of child development. Children having cerebral paralysis present different clinical manifestations, but all present damage of neurological function. Cerebral paralysis is an extremely disable disease, the world incidence is 2,5 per 1000 newborns in developing countries and 2,0 per 1000 newborns in developed nations. Objective: to identify feeding and nutritional characteristics in children having cerebral paralysis in order to develop guidelines for health professionals working with these children. Methods: a systematic search of articles published the last 10 years related to the topic was done, looking in scientific national and international data base. Results: cerebral paralysis affects physiological functions like suction, mastication, swallowing and breading system, that affect feeding process and nutritional status of children. Conclusion: the main purpose of this review was to understand the impact of cerebral paralysis on nutritional status in children having this syndrome, also this review provides information about recommendations that health professionals should apply to improve the quality of life for this population. Key words: cerebral palsy, diet, nutrition, dysphagia, children.